2013
DOI: 10.1017/s0007485313000035
|View full text |Cite
|
Sign up to set email alerts
|

Lysiphlebus orientalis (Hymenoptera, Braconidae), a new invasive aphid parasitoid in Europe – evidence from molecular markers

Abstract: We report the occurrence of Lysiphlebus orientalis in Serbia, an aphid parasitoid from the Far East that is new to Europe and has the potential to become invasive. Our finding based on morphological characters is confirmed by analyses of mitochondrial cytochrome oxidase subunit I sequences. An increase in number and an expansion of the host range were observed during field studies over the past two years, and it is determined that the current host range encompasses nine aphid hosts on 12 different host plants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Lysiphlebus orientalis Starý & Rakhshani (Hymenoptera: Braconidae) is a recently described thelytokous parthenogenetic parasitoid wasp collected from soybean aphid's native range in China and held in quarantine as a potential biological control agent of soybean aphid (Starý et al., ). Lysiphlebus orientalis has also recently been found in Serbia, where it is considered potentially invasive (Petrović et al., ). This endoparasitoid is a solitary koinobiont, so the aphid continues to develop temporarily after parasitism and a single aphid individual can only support the development of one parasitoid individual (Godfray, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysiphlebus orientalis Starý & Rakhshani (Hymenoptera: Braconidae) is a recently described thelytokous parthenogenetic parasitoid wasp collected from soybean aphid's native range in China and held in quarantine as a potential biological control agent of soybean aphid (Starý et al., ). Lysiphlebus orientalis has also recently been found in Serbia, where it is considered potentially invasive (Petrović et al., ). This endoparasitoid is a solitary koinobiont, so the aphid continues to develop temporarily after parasitism and a single aphid individual can only support the development of one parasitoid individual (Godfray, ).…”
Section: Methodsmentioning
confidence: 99%
“…Adult wasps were used in experiments 24–48 h after emergence. As L. orientalis is thelytokous (Starý et al., ; Petrović et al., ), there was no need to track mating status.…”
Section: Methodsmentioning
confidence: 99%
“…In the past decade, DNA barcoding has been widely used in identification of Hymenoptera parasitoids (Derocles et al ., ; Smith et al ., ; Novković et al ., ; Babcock & Heraty, ; Ratcliffe et al ., ; Jinbo et al ., ; Zhang et al ., ; Chester et al ., ; Emam et al ., ). Recent studies of soybean aphid parasitoids (Wyckhuys & Heimpel, ; Wyckhuys et al ., ; Starý et al ., ; Wu et al ., ; Desneux et al ., ; Petrović et al ., ) indicated that DNA barcoding may be a useful tool for their identification.…”
Section: Introductionmentioning
confidence: 99%
“…Viewed from this perspective, more research is needed to determine whether T. sunnysidensis could play a significant role in the biological control of this aphid. As with all biological control attempts, this should involve extensive testing because there are recorded cases of parasitoids becoming widespread after their introduction and expanding their host range in non‐native areas, regardless of whether the introduction was intentional or not (Roy et al , ; Mitrović et al , ; Petrović et al , ). The importance of understanding the genetic structure of both pest species and their natural enemies in biological control programmes has now been recognized in numerous studies (Roderick & Navajas, ; Lozier et al , ; Muirhead et al , ; Tavares et al , ; Andersen & Wagner, ).…”
Section: Discussionmentioning
confidence: 99%